2017
DOI: 10.2147/ott.s138908
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of EGF-β-catenin signaling in the epithelial-mesenchymal transition in human glioblastoma

Abstract: To date, β-catenin has been reported to be implicated in mediating the epithelial-mesenchymal transition (EMT) in a variety of human cancers, which can be triggered by EGF. However, the mechanisms underlying EGF-β-catenin pathway-induced EMT of glioblastoma multiforme (GBM) have not been reported previously. In the present study, immunohistochemistry, reverse transcription polymerase chain reaction, and Western blot were applied to investigate the effect of EGF-β-catenin pathway on EMT of GBM. Here, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Furthermore, inhibition of TRPM7 expression by MK886 also significantly attenuated the EGF-induced migration, invasion and wound healing of ovarian cancer cells by inhibiting the EMT process. Such data support the notion that higher levels of TRPM7 expression are associated with the metastasis of ovarian carcinoma [3638]. Hence, TRPM7 may be new therapeutic target for prevention and intervention of ovarian cancer metastasis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, inhibition of TRPM7 expression by MK886 also significantly attenuated the EGF-induced migration, invasion and wound healing of ovarian cancer cells by inhibiting the EMT process. Such data support the notion that higher levels of TRPM7 expression are associated with the metastasis of ovarian carcinoma [3638]. Hence, TRPM7 may be new therapeutic target for prevention and intervention of ovarian cancer metastasis.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that EGF is crucial for the migration, invasion and wound healing [3638] and both F-actin and Vinculin regulate the cytoskeletal remodeling and cell-cell adhesion, to promote cell migration movement [39, 40]. In this study, we found that TRPM7 silencing by specific shRNA significantly decreased the levels of TRPM7 expression and attenuated the EGF-induced migration, invasion and wound healing of ovarian cancer cells in vitro.…”
Section: Discussionsupporting
confidence: 53%
“…Some studies have reported that the Wnt pathway plays an important role in promoting EMT and angiogenesis in cancer. Overexpression of Wnt3 ligand activated the Wnt/β-catenin pathway, whereas epidermal growth factor (EGF) secretion activated PI3K/Akt pathways, which accounted for β-catenin accumulation and mediated EMT and angiogenesis [35,36,37]. Since β-catenin is a major protein in the Wnt signaling pathway, targeting Wnt signaling can be a good strategy to control EMT and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other tumors, Wnt pathway is constitutively active in GBM and its deregulation is likely responsible for initiation and/or progression of the disease [150,151,152,153]. β-catenin translocation to the nucleus characterizes the mesenchymal and invasive phenotype of tumoral cells as it promotes SNAIL and ZEB1 transcription and mediates EGFR pathway-induced EMT [154,155,156].…”
Section: Autophagy and Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%